2021
DOI: 10.28932/jam.v13i1.2700
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Akurasi Model Altman Modifikasi (Z”-Score), Zmijewski, Ohlson, Springate dan Grover Untuk Memprediksi Financial Distress Klub Sepak Bola

Abstract: This study aims to find an accurate financial difficulty prediction model in English Premier League football, and also to compare with previous research so as to obtain the results of a financial difficulty prediction model that can be used for all football clubs. The way to determine the sample to be examined is using purposive sampling technique with a population of 49 English premier league clubs from 1992-2018, so that the number of samples obtained is 37 samples and then grouped in the categories of finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
1
1
3
Order By: Relevance
“…The following is a comparison of the results of the accuracy calculations of the prediction models: (Humairoh et al, 2022) that the Altman prediction model has the highest level of accuracy in predicting financial distress. However, the results of this research contradict research conducted by Lutfiyyah and Bhilawa (2021), reseach by Lestari (2022) and research by Zidane and Tojibussabirin (2022) which shows that the Zmijewski model received the highest level of accuracy. Apart from that, the results of this study also contradict research conducted by Stankevičienė and Prazdeckaitė (2021) showing that the Ohlson and Zmijewski model shows the greatest accuracy for predicting bankruptcy.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The following is a comparison of the results of the accuracy calculations of the prediction models: (Humairoh et al, 2022) that the Altman prediction model has the highest level of accuracy in predicting financial distress. However, the results of this research contradict research conducted by Lutfiyyah and Bhilawa (2021), reseach by Lestari (2022) and research by Zidane and Tojibussabirin (2022) which shows that the Zmijewski model received the highest level of accuracy. Apart from that, the results of this study also contradict research conducted by Stankevičienė and Prazdeckaitė (2021) showing that the Ohlson and Zmijewski model shows the greatest accuracy for predicting bankruptcy.…”
Section: Discussioncontrasting
confidence: 93%
“…In previous studies, several researchers have revealed various results related to predicting financial distress, as in research by Puro et al (2019) for the hospital industry, showing that the modified Altman model had the highest level of accuracy, namely 88.67%. Likewise, research by Humairoh et al (2022) stated that the Altman model had the most significant level of accuracy in predicting companies that had been delisted from the Indonesian Stock Exchange, and Lutfiyyah and Bhilawa (2021), whose research referred to English football clubs, resulted in the Zmijewski model showing the highest level of accuracy, namely 72%. Research Lestari (2022), which applied this model to companies in the property and real estate sub-sector, also showed the same results and research conducted by Zidane and Tojibussabirin (2022) at PT Garuda Indonesia stated that the Zmijewski model had the highest level of accuracy, namely 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Mark melakukan penelitian dengan menggunakan sampel sebanyak 840 perusahaan yang terdaftar di American and New York Stock Exchanges tahun 1972-1978 yang terdiri dari 40 perusahaan yang mengalami kebangkrutan dan 800 perusahaan yang aman. Berdasarkan penelitian tersebut, diperoleh tingkat akurasi sebesar 99% (Lutfiyyah dan Bhilawa, 2021). Rasio keuangan yang digunakan pada model ini dipilih dari rasio keuangan yang telah digunakan pada penelitian terdahulu yang meliputi rasio profitabilitas yang diukur melalui Return on Asset (ROA), rasio solvabilitas yang diukur melalui Debt to Asset Ratio (DAR), dan rasio likuiditas…”
Section: Model Zmijewskiunclassified
“…Tahun 1984, Mark E. Zmijewski melakukan penelitian terhadap 840 perusahaan yang terdaftar di American and New York Stock Exchanges tahun 1972-1978 yang terdiri dari 40 perusahaan yang mengalami kebangkrutan dan 800 perusahaan yang aman. Berdasarkan penelitian tersebut, diperoleh tingkat akurasi sebesar 99% (Lutfiyyah dan Bhilawa, 2021). Perbedaan tingkat akurasi dari ketiga model prediksi kebangkrutan menyebabkan perlu adanya uji perbandingan hasil prediksi kebangkrutan dari ketiga model prediksi kebangkrutan tersebut.…”
Section: Perbedaan Tingkat Prediksi Model Kebangkrutan Perusahaanunclassified
See 1 more Smart Citation